2018
DOI: 10.1016/j.bbmt.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Advanced Hodgkin Lymphoma after Umbilical Cord Blood Transplantation: A Eurocord and EBMT Lymphoma and Cellular Therapy & Immunobiology Working Party Study

Abstract: Allogeneic stem cell transplantation is an alternative for patients with relapsed or refractory Hodgkin lymphoma (HL), but only limited data on unrelated umbilical cord blood transplantation (UCBT) are available. We analyzed 131 adults with HL who underwent UCBT in European Society for Blood and Marrow Transplantation centers from 2003 to 2015. Disease status at UCBT was complete remission (CR) in 59 patients (47%), and almost all patients had received a previous autologous stem cell transplantation. The 4-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…The recorded high incidence of transplantation-related mortality after UCB transplantation is consistent with other reports. [3][4][5]10 Several factors may have contributed to the higher transplantation-related mortality, including higher grade 3-4 acute and chronic GVHD, higher incidence of bacterial and viral infections, 21 and HLA disparity. 22 Most UCB transplantations were mismatched at 2 HLA loci considering lower resolution HLA match and, therefore, likely to be mismatched at $ 3 HLA loci considering allelelevel match.…”
Section: Probability (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…The recorded high incidence of transplantation-related mortality after UCB transplantation is consistent with other reports. [3][4][5]10 Several factors may have contributed to the higher transplantation-related mortality, including higher grade 3-4 acute and chronic GVHD, higher incidence of bacterial and viral infections, 21 and HLA disparity. 22 Most UCB transplantations were mismatched at 2 HLA loci considering lower resolution HLA match and, therefore, likely to be mismatched at $ 3 HLA loci considering allelelevel match.…”
Section: Probability (%)mentioning
confidence: 99%
“…Both donor sources are readily available, tolerance has been demonstrated for donorrecipient HLA disparity, and reports suggest comparable outcomes between the 2 donor types for hematologic malignancy. [2][3][4][5][6][7][8][9][10][11] Donor selection (UCB or haploidentical relative) is often based on transplantation center experience, donor availability, and the cost associated with transplantation, although there are no comparative economic analyses to date. However, several reports included heterogenous conditioning regimens and graft-versus-host disease (GVHD) prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…The 4-year relapse rate, NRM, PFS and OS were 44%, 31%, 26%, and 46%, respectively. Having residual disease at the time of transplant was associated with worse outcomes, while receiving RIC regimen of cyclophosphamide, fludarabine, and low dose total body irradiation was associated with better PFS and OS in multivariate analysis [45].…”
Section: Role Of Alternative Donor Hsct In Relapsed or Refractory Chlmentioning
confidence: 95%
“…The retained hypothesis is that the long half-life of nivolumab and pembrolizumab in the plasma would induce a persistent T cell activation of donor-derived immune cells increasing the risk of severe acute and chronic GvHD, immune-mediated pneumonia and other organ-related immune alterations in the recipient. Some translational data have attempted to explain the pathophysiology of these complications and biological analyses of a multicenter retrospective study conducted on 39 patients who received PD-1 blockade before allo-HCT have shown a significant reduction in PD-1 T cells and decreased Tregs as compared with the historical cohort of patients who did not receive checkpoint inhibitors [ 138 ]. An interesting study conducted by the Spanish group from the University of Barcelona, showed that nivolumab may persist in the blood until 56 days after transplant and that while patients receiving only calcineurin inhibitors had an increased incidence of severe acute GvHD and a more effector T cell profile, patients undergoing PT-Cy had a similar risk of GVHD and similar T cell profile to those without previous nivolumab exposure [ 139 ].…”
Section: Management Of Relapsed/refractory Hodgkin Lymphomamentioning
confidence: 99%